Patients’ perception of quality of tuberculosis healthcare service in South West Nigeria - Oyebade, Akin; Adeola, Olatoun; Akinmurele, Timothy; Taiwo, Olaniyi; Oginni, Adeniyi; Adekunle, Isiaka; Gbadamosi, Maroof (International Journal Of Community Medicine And Public Health, 2023)
Background: Nigeria has the highest burden of tuberculosis (TB) in Africa and is among the 14 countries in all the 3 world health organization global high-burden countries for TB, TB/HIV and MDR-TB. The aim of this study was to assess patients’ perception of the quality of TB healthcare in Southwest Nigeria Methods: The study utilized the cross-sectional design, and data was collected from drug-sensitive TB clients receiving care at health facilities providing TB healthcare services Results: The average time clients spent to get to TB facilities from home was 23 minutes, the average waiting time was 6.7 minutes, and the average medical visit time was 17 minutes. Sixty-seven percent of respondents strongly agreed that doctors explained medical test result with them and 68.7% strongly agree that they wanted the medical doctors to spend more time with them. The mean score for convenience of accessing drugs was 4.8±0.5 mins, mean score for convenience of accessing laboratory test was 4.7±0.6 mins and mean score for convenience of accessing chest x-ray was 3.8±1.4 mins. Overall, the quality of TB care was perceived to be good. Conclusions: Overall, the quality of TB services is very good from the perspectives of the patient, however, there is need to improve integrated patient-centered TB healthcare services by medical doctors. In addition, access to chest x-ray services should be improved to enhance quality of TB services.